Seroprevalence and haemato-biochemical effects of bovine leucosis in buffalo, Punjab, Pakistan - A Rahman; M Kashif; A Nasir; S Ehtisham-ul-Haque; H Ullah; A Sikandar; I Ahmed; AU Rehman; MA Saeed; MW Nazar; M Rizwan; S Saher; et al. (Veterinární Medicína, 2023)
Enzootic bovine leucosis is caused by bovine leukaemia virus (BLV), a Deltaretrovirus belonging to the family Retroviridae. BLV causes huge economic losses to the dairy industry in the form of decreased milk production, premature culling, and poor reproductive performance of the animals. The aim of the present study was to determine the seroprevalence of BLV infection in buffalo in two districts of Punjab, Pakistan. A total of 384 samples were collected and analysed using a commercial indirect enzyme-linked immunosorbent assay (ELISA) to investigate the seroprevalence of BLV through the detection of the anti-BLV gp51 antibody. A predesigned data questionnaire proforma was employed to find out the association of risk factors with disease. Overall, 18.2% of buffaloes were seropositive for BLV in the study population. The results revealed a significant association (P < 0.05) of age with BLV infection. Furthermore, milk yield and pregnancy had a significant association with the seroprevalence of BLV infection in buffalo whereas no significant association was found with sex, breeding, and health status. Biochemical and oxidative stress markers revealed a significant decrease in liver enzymes alanine transaminase (ALT) and aspartate transaminase (AST), glutathione peroxidase (GPX), and superoxide dismutase (SOD) in seropositive animals as compared to healthy animals. It is concluded that BLV has a considerable prevalence in buffalo in Punjab, Pakistan and there is a dire need to investigate the disease epidemiology at both national and international levels and strategies should be developed to implement an effective control program.